A Targeted Mass Spectrometric Analysis Reveals the Presence of a Reduced but Dynamic Sphingolipid Metabolic Pathway in an Ancient Protozoan, Giardia lamblia - Duarte, Trevor T.; Ellis, Cameron C.; Grajeda, Brian I.; De Chatterjee, Atasi; Almeida, Igor C.; Das, Siddhartha (Frontiers in Cellular and Infection Microbiology, 2019)
Giardia lamblia, a single-celled eukaryote, colonizes and thrives in the small intestine of humans. Because of its compact and reduced genome, Giardia has adapted a “minimalistic” life style, as it becomes dependent on available resources of the small intestine. Because Giardia expresses fewer sphingolipid (SL) genes—and glycosphingolipids are critical for encystation—we investigated the SL metabolic cycle in this parasite. A tandem mass spectrometry (MS/MS) analysis reveals that major SLs in Giardia include sphingomyelins, sphingoid bases, ceramides, and glycosylceramides. Many of these lipids are obtained by Giardia from the growth medium, remodeled at their fatty acyl chains and end up in the spent medium. For instance, ceramide-1-phosphate, a proinflammatory molecule that is not present in the culture medium, is generated from sphingosine (abundant in the culture medium) possibly by remodeling reactions. It is then subsequently released into the spent medium. Thus, the secretion of ceramide-1-phospate and other SL derivatives by Giardia could be associated with inflammatory bowel disease observed in acute giardiasis. Additionally, we found that the levels of SLs increase in encysting Giardia and are differentially regulated throughout the encystation cycle. We propose that SL metabolism is important for this parasite and, could serve as potential targets for developing novel anti-giardial agents.